Polymer-based microparticles in tissue engineering and regenerative medicine - Oliveira, Mariana B. (2011)
Different types of biomaterials, processed into different shapes, have been proposed as temporary support for cells in tissue engineering (TE) strategies. The manufacturing methods used in the production of particles in drug delivery strategies have been adapted for the development of microparticles in the fields of TE and regenerative medicine (RM). Microparticles have been applied as building blocks and matrices for the delivery of soluble factors, aiming for the construction of TE scaffolds, either by fusion giving rise to porous scaffolds or as injectable systems for in situ scaffold formation, avoiding complicated surgery procedures. More recently, organ printing strategies have been developed by the fusion of hydrogel particles with encapsulated cells, aiming the production of organs in in vitro conditions. Mesoscale self-assembly of hydrogel microblocks and the use of leachable particles in three-dimensional (3D) layer-by-layer (LbL) techniques have been suggested as well in recent works. Along with innovative applications, new perspectives are open for the use of these versatile structures, and different directions can still be followed to use all the potential that such systems can bring. This review focuses on polymeric microparticle processing techniques and overviews several examples and general concepts related to the use of these systems in TE and RE applications. The use of materials in the development of microparticles from research to clinical applications is also discussed.